Decoding Pain Dynamics: EEG Insights into Neural Responses and Classification via RQA Analysis - Mahsa Tavasoli; Zahra Einalou; Reza Akhondzadeh (Frontiers in Biomedical Technologies)
Purpose: Pain is an unpleasant sensation that is important in all therapeutic conditions. So far, some researches have been done on pain assessment and cognition, and researchers have come to evaluate pain through different tests and methods. Since the occurrence of pain causes along with activation of a long network in brain regions, so recognition of dynamical changes of the brain in pain states is helpful for pain detection using Electroencephalogram (EEG) signal.